2019
DOI: 10.3390/agronomy9110689
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Variation in Cotton Genotypes for Phosphorus-Use Efficiency

Abstract: Low phosphorus (P) availability is a major constraint for cotton production. Consequently, P-efficient genotypes can improve productivity under conditions where the higher application of P is not economical. This study was conducted to characterize cotton genotypes for P-use efficiency under various P concentrations (0, 10, 20, 40, 80, and 500 μM KH2PO4). The results showed large genotypic variation in five selected traits, such as root dry weight, shoot dry weight, photosynthetic activity, P-utilization effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 47 publications
3
33
0
Order By: Relevance
“…The increase in these morphological traits in N-efficient genotypes might be due to improve N uptake, photosynthetic activity, and N metabolism. The current results are consistent with the previous studies performed on Arabidopsis [11], maize [38], tomato [19], and cotton [39], where efficient genotypes performed better than inefficient genotypes. In addition, ANOVA showed that the genotypic effects accounted for 5%-30% of the total variance, suggesting that cotton genotypes have significant variations in morphological traits.…”
Section: Variations In Morphophysiological and Biochemical Traits Amosupporting
confidence: 93%
See 2 more Smart Citations
“…The increase in these morphological traits in N-efficient genotypes might be due to improve N uptake, photosynthetic activity, and N metabolism. The current results are consistent with the previous studies performed on Arabidopsis [11], maize [38], tomato [19], and cotton [39], where efficient genotypes performed better than inefficient genotypes. In addition, ANOVA showed that the genotypic effects accounted for 5%-30% of the total variance, suggesting that cotton genotypes have significant variations in morphological traits.…”
Section: Variations In Morphophysiological and Biochemical Traits Amosupporting
confidence: 93%
“…The previous study showed a positive correlation between leaf N concentration and photosynthesis [43,44] and, consistently, a positive correlation was noted between N concentration and photosynthetic activity (r = 0.93). Similarly, the increasing trend of photosynthesis with N supply in N-efficient genotype (CCRI-69) was consistent with our previous results [39], as well as results in poplar species [45,46]. Conversely, the photosynthetic activity in N-inefficient genotypes especially XLZ-30 decreased, which might have been due to inhibition in the photosystem, as many genes involved in the photosystem were downregulated under contrasting nitrogen supply [46].…”
Section: Variations In Morphophysiological and Biochemical Traits Amosupporting
confidence: 91%
See 1 more Smart Citation
“…The average of all the plants from treatments was worked out for mean shoot length. Similarly, lengths and widths of each leaf of six randomly selected plants were measured, then the mean single leaf area was calculated [66]. At the end of the experiment, seedlings were harvested and separated into shoot and roots, placed in labeled paper bags.…”
Section: Plant Growth and Root Morphologymentioning
confidence: 99%
“…25 Similarly, the lengths and widths of each leaf were measured and the mean single leaf area was obtained from the product of length, width and correction factor (0.75). 26 The harvested plants were then put in the oven at 105°C for 1 h followed by 80°C for 48 h. The shoot and total plant dry weight of each plant was measured with the help of an electronic balance. At the end of the experiment, the root morphological parameters were measured by using a special image analysis software program WinRHIZO (Win/Mac RHIZO Pro V. 2002c Regent Instruments Inc., Québec, QC G1V 1V4, Canada) in combination with Epson Expression 11000XL scanner.…”
Section: Wileyonlinelibrarycom/jsfamentioning
confidence: 99%